Healthcare Professional’s Perception of Patient Safety Measured by the Hospital Survey on Patient Safety Culture: A Systematic Review and Meta-Analysis - Julia Hiromi Hori Okuyama; Tais Freire Galvao; Marcus Tolentino Silva (The Scientific World Journal)
Objective. To assess the culture of patient safety in studies that employed the hospital survey on patient safety culture (HSOPS) in hospitals around the world. Method. We searched MEDLINE, EMBASE, SCOPUS, CINAHL, and SciELO. Two researchers selected studies and extracted the following data: year of publication, country, percentage of physicians and nurses, sample size, and results for the 12 HSOPS dimensions. For each dimension, a random effects meta-analysis with double-arcsine transformation was performed, as well as meta-regressions to investigate heterogeneity, and tests for publication bias. Results. 59 studies with 755,415 practitioners surveyed were included in the review. 29 studies were conducted in the Asian continent and 11 in the United States. On average studies scored 9 out of 10 methodological quality score. Of the 12 HSOPS dimensions, six scored under 50% of positivity, with “nonpunitive response to errors” the lowest one. In the meta-regression, three dimensions were shown to be influenced by the proportion of physicians and five by the continent where survey was held. Conclusions. The HSOPS is widely used in several countries to assess the culture of patient safety in hospital settings. The culture of culpability is the main weakness across studies. Encouraging event reporting and learning from errors should be priorities in hospitals worldwide.